Hyperskewness of (1 + 1)-dimensional KPZ height fluctuations. (28th January 2016) - Singha, Tapas; Nandy, Malay K
Abstract: We evaluate the fifth-order normalised cumulant, known as hyperskewness, of height fluctuations dictated by the (1  +  1)-dimensional KPZ equation for the stochastic growth of a surface on a flat geometry in the stationary state. We follow a diagrammatic approach and invoke a renormalisation scheme to calculate the fifth cumulant given by a connected loop diagram. This, together with the result for the second cumulant, leads to the hyperskewness value .